Improving the Learning Outcomes of Natural and Social Science (IPAS) through Diorama Media: A Meaningful Learning Study at Madrasah Ibtidaiyah - Farda, Ummu Jauharin; Fitria Martanti; Ana Quthratun Nada; Dwi Pitriani (UIN Sunan Kalijaga Yogyakarta, 2025)
Diorama media is one of the learning facilities that can be used effectively in learning IPAS at the Madrasah Ibtidaiyah level. This medium has the advantage of presenting abstract concepts, such as the water cycle, in be more concrete and easier-to-understand way for students through three-dimensional visualization. The primary purpose of this study is to observe changes in students' understanding of water cycle aterials before and after the use of diorama media. This study uses a quantitative approach with an experimental method that applies to the One Group Pretest-Posttest Design. All students of class V MI, As Salam Karangawen, went through a total sampling technique. Data was collected using written tests in the form of pretests and posttests to measure the improvement of learning outcomes, observations to see the process and involvement of students in learning, and documentation as supporting data. The results of the study show two main findings. First, the use of diorama media has proven to be effective in improving student learning outcomes in science subjects. This is proven by the average N-Gain obtained, which is 0.6764 or the equivalent of 67. 64%. Based on the N-Gain score interpretation table, this value is in the range of 56-75% which is included in the ”fairly effective” category . Second, this media can create more meaningful learning, where students can relate the concepts learned to real phenomena in daily life.